Morpho-Physiology and Yield Alterations in the Four Chili Varieties (Capsicum annuum L.) in Various Soil Depth Media in Tropical Lowland - Sulistyaningsih, Endang; Kusumaningrum, Sarlin; Murti, Rudi Hari (Trends in Sciences, 2025)
Chilies (Capsicum annuum L.) cultivated in lowland areas of Indonesia typically exhibit lower yields compared to those grown in highland regions. Chili growth and yield can be optimized by modifying the growing medium. This research aimed to determine the changing morpho-physiology and yield of four chili varieties in various soil depth media planted in tropical lowlands. The factorial treatments were arranged in a completely randomized design with 240 chili plants for 8 combination treatments. The first factor was the chili variety: Kencana, Lembang-1, Tanjung-2, and Ungara. The second factor was the soil depth media, consisting of 25- and 30-cm soil depth media. Data in morpho-physiology and yield were analyzed using factorial analysis of variance (ANOVA) based on a completely randomized design (CRD), followed by an Honestly Significant Difference (HSD) test at a 95% confidence interval. The results showed that the fruit yield in Lembang-1, Tanjung-2, and Ungara responded positively by 15.20%, 7.80%, and 8.11%, respectively, under 30 cm compared to the 25 cm soil depth media. However, the yield in Kencana responded negatively by 8.29%, due to new vegetative growth. In the responsive varieties, enhanced chili yield was related to the improvement of morpho-physiology through increased root length, root surface area, and root:shoot ratio, as well as shoot dry weight and leaf area, total chlorophyll content, net assimilation rate, and relative growth rate of the plant. It was concluded that soil media up to a 30 cm depth is recommended to improve yield in Lembang-1, Tanjung-2, and Ungara, in tropical lowland. HIGHLIGHTS Chili plants have a taproot system and grow in tropical lowland, with root lengths ranging from 4,177 to 7,642 cm, depending on the varieties. Therefore, it is important to evaluate the increment of soil depth for chili plant cultivation up to 30 cm to facilitate root development of chili for enhancing chili yield. This research provides information on chili yield and morpho-physiological responses of different soil depth conditions in tropical lowland areas. Results showed that fruit yields of Lembang-1, Tanjung-2, and Ungara increased by 15.20%, 7.80%, and 8.11%, respectively, under 30 cm soil depth compared to 25 cm, unlike in Kencana. The varieties in which the yield improved in response to 30 cm soil depth were related to enhanced root architecture (total root length and root surface area), increased shoot dry weight, leaf area, total chlorophyll content, net assimilation rate, and relative growth rate. Therefore, a soil depth of 30 cm is recommended to improve yield in Lembang-1, Tanjung-2, and Ungara, in tropical lowland areas. GRAPHICAL ABSTRACT